Online career construction for a trauma survivor with career choice ambivalence - Maree, J. G. (South African Journal of Higher Education, 2024)
This article reports on the online administration of career construction counselling for a trauma survivor who sought help in resolving her career-choice ambivalence (uncertainty). The participant was purposively selected from a group of people attending a workshop on career construction counselling. An intrinsic, descriptive, exploratory intervention case study based on career construction counselling (involving administering the Career Construction Interview (CCI) to elicit the participant’s micro-narratives qualitatively) was used to generate data and adapted thematic data analysis incorporating the analytic style proposed by Savickas was used to analyse the data reflexively. The intervention shed light on the participant’s conscious knowledge about herself and on her subconsciously regulated views on her preferred future career choices. The findings confirmed the value of career construction counselling in promoting the participant’s psychological self as an autobiographical author especially. They also underlined the importance of timely intervention for trauma survivors in pre-empting the occurrence of unmastered developmental tasks and repetition of trauma. Future research should involve diverse participants in individual as well as group contexts. Equally important is contextualising the intervention discussed here to meet the distinctive diversity needs of participants in individual and group contexts.